Análise do planejamento ferroviário: uma abordagem utilizando simulação de eventos discretos - Faria, Carlos Henrique Fernandes de (2016)
The growth and the search for the rail transportation over the past few years make logistics decisions impacting on the business of the companies. Also, logistics has a fundamental importance and considerable cost and then receives special attention to managerial level. In the railway, changes in the long and medium-term system infrastructure as the construction of crossing yards, duplications or triplications on the track, the improvements of the rail to increase velocity of the compositions , as fixed costs and short-term decisions, such as the conservation of the wagons and locomotives, fuel expenses and the operacional workers necessary for efficient operation, require high costs and investments. Thus, the analysis need special attention in how they are made and then, what tools are using for decision making. In this context, the study aims to develop a discrete event simulation tool supply chain closed loop iron ore, capable of supporting analysis in the three planning levels. At the strategic level, with the perfect amount of setting wagons on the railway to make the projected volume in the long term and increase the rail capacity with the integration of investment projects in duplicate and simple railway. At the tactical level, the definition of railway stretch capabilities using dynamic simulation. And at the operational level, with the definition of the best maintenance strategies programmed permanent way that impact least some variables as the transit time and capacity. As a result, it was observed that the results obtained by the developed simulation tool are well adherent to the real system, bringing answers with low standard deviation and error rates when considering an accuracy in the results of 95%.